Case Western Reserve University School of Law’s Academy for Inclusive Leadership Development: A New Pedagogy Integrating Diversity, Equity, and Inclusive Belonging into Legal Education - Bryan L. Adamson (Washington University Journal of Law and Policy, 2024)
This essay outlines the blueprint for The Academy for Inclusive Leadership Development at Case Western Reserve University School of Law. Created in response to the national, racialized police brutality of The Racial Reckoning in summer 2020, The Academy seeks to equip legal professionals and students with tools to identify, assess, and reform policies and practices which perpetuate systemic inequality in the legal profession and education. The architects of The Academy argue that cycles of neutral stances on critical matters that impact the law, legal institutions and the workplace without progressive effective responses cannot sustain the needs of the legal profession in the future. The Academy implements a proactive, leadership-based training model that aims to eradicate stereotypes and mitigate micro-aggressions and biases in the workplace and classroom. Ultimately, The Academy seeks to empower legal professional to take leadership roles in order to create diverse, supportive, and engaging workplaces.
Keywords: InclusiveLeadership; SystemicEquality; DiversityInLaw; ProactiveTraining; WorkplaceBiasMitigation